Terminología bilingüe (francés-español) en los servicios públicos: el ámbito de la Ley de Dependencia - Marc Martínez, Isabelle; Maroto García, Nava (Anales de Filología Francesa, 2010)
This article aims at analysing, collecting and presenting the basic terminology related to dependent care, according to the provisions of the Spanish law 39/2006, of 14 December about promotion of personal autonomy and care for people in a situation of dependency. In the context of public services translation and interpreting, it becomes necessary to define the adequate terminology related to the law and its implementation in a highly precise way, as well as presenting the equivalents in the languages used in Spain. We thus suggest a compilation of bilingual terminology (Spanish-French) collected taking into account the nature of its end-users: public services translators and interpreters, cultural mediators and migrant people living in Spain who are willing to access the services and assistance envisaged in the aforementioned Law.